Human resource management and entrepreneurship fit: a systematic review of literature . - Mathushan, P.; Pushpanathan, A. (Faculty of Management Studies, Rajarata University of Sri Lanka., 2020)
Over the decades, the exponential competitive rivalry among the firms combined with the technological changes have rushed firms to pursue sophisticated techniques for reaping competitive advantage. Organizations have been starving to enhance their adaptability, innovation, creativity, risk taking, and entrepreneurship have become the invader in the competition. Although there are many factors impact on organizational entrepreneurship, Human Resource Management is indispensable. Precisely, it’s the fundamental duty of an entrepreneur to recruit, manage, motivate, reinforce, satisfy, retain and maintain human resources to enhance entrepreneurial success and growth. It is imperative to comprehend the role of Human Resource Management in developing sustainable entrepreneurship and entrepreneurial ventures. Moreover, knowing how Human Resource Management practices and procedures can be used to assist accelerate the changing landscape in entrepreneurial firms. This study investigates the consequences and relationship between human resource practices and entrepreneurial success. Thus, it embraces conceptual analysis of the Human Resource Management practices espoused by entrepreneurs and to analyze the interrelationship between human resource practices and entrepreneurship in spite of success, through literature and how far this research has progressed. Drawing on large corpus of the research, the study found that the entrepreneurs embrace the significant Human Resource Management practices fostering entrepreneurial success effectively and efficiently. Notwithstanding, results manifest that human is more vital rather than money for entrepreneurs. Intriguingly, entrepreneurs should possess sufficient level knowledge and understanding on Human Resource Management and its functions.
Keywords: Competencies.; Entrepreneur; Entrepreneurial success; Entrepreneurship; Human resource practices